CRISPR/Cas9-mediated targeted gene correction in amyotrophic lateral sclerosis patient iPSCs. Issue 5 (11th April 2017) - Wang, Lixia; Yi, Fei; Fu, Lina; Yang, Jiping; Wang, Si; Wang, Zhaoxia; Suzuki, Keiichiro; Sun, Liang; Xu, Xiuling; Yu, Yang; Qiao, Jie; Belmonte, Juan Carlos Izpisua; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a complex neurodegenerative disease with cellular and molecular mechanisms yet to be fully described. Mutations in a number of genes including SOD1 and FUS are associated with familial ALS. Here we report the generation of induced pluripotent stem cells (iPSCs) from fibroblasts of familial ALS patients bearing SOD1 +/ A272C and FUS +/ G1566A mutations, respectively. We further generated gene corrected ALS iPSCs using CRISPR/Cas9 system. Genome-wide RNA sequencing (RNA-seq) analysis of motor neurons derived from SOD1 +/ A272C and corrected iPSCs revealed 899 aberrant transcripts. Our work may shed light on discovery of early biomarkers and pathways dysregulated in ALS, as well as provide a basis for novel therapeutic strategies to treat ALS.